EXPLOITATION AND PROTECTION OF TURTLES AT SERANGAN AND TANJUNG BENOA VILLAGES SOUTH BALI IN THE PERSPECTIVE OF CULTURAL STUDIES - Sudiana, I Gusti Ngurah; Ardika, I Wayan; Parimartha, I Gde; Titib, I Made (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2009)
The people at Serangan and Tanjung Benoa Villages have a habit to kill turtles for sale,consumption, custom and religion. They were all restless when their habit was hegomonized bythe government by applying the Act concerning scarce animal conservation. The people urgedthat they be provided with freedom in killing turtles, but the government still intends to stopkilling turtles at the two villages. The two different interests have resulted in a controversy overthe exploitation of turtles making the Bali community as a whole called the killers of turtles.The title of this study is the Exploitation and Protection of Turtles at Serangan andTanjung Benoa Villages, South Bali: in the Perspective of Cultural Studies. The subjectsdiscussed are how the exploitation and protection of turtles implemented, what factorsmotivating their exploitation and protection, what meaningfulness is made to appear by theirexploitation and protection.Qualitative method was used. The data needed were collected by interview,observation, documentation of the secondary data. The data were descriptively and qualitativelyanalyzed using the theory of discourse, the theory of deconstruction, the theory of hegemony andthe perspective of cultural studies.The research findings show that before the Acts Number 7 and 8 of 1999 concerningconservation of scarce animals, exploitation of turtles was part of the people’s life in South Bali.However, after 2005, such constitution has changed from being done in an extractive way tobeing done in a non-extractive way. Meaningfulness to turtles has also changed, from beingexploited to being conserved. Such a conservation has been done by releasing tukiks ( turtles’babies) to the sea. Since 2005, a change has also taken place with regard to the turtles killed forreligious and traditional ceremonies. Formerly, many big turtles were used for religious andtraditional ceremonies, but now only a few and small ones are used. If none is found, ducks areused to replace the turtles.